IMPACT OF ANESTHESIA METHODS ON CENTRAL HEMODYNAMICS AND CEREBRAL BLOOD FLOW DURING CAROTID ENDARTERECTOMY - Neymаrk, M. I.; Shmelev, V. V.; Shаydurov, А. А.; Shаdymov, B. А. (Vestnik anesteziologii i reanimatologii, 2018)
The objective: to compare the impact of two methods of general anesthesia during carotid endarterectomy on central hemodynamics and cerebral blood flow in order to choose the best anaesthesiologic tactics. Materials and subjects. The total intravenous anesthesia (sedation with propofol, n = 60) and general combined anesthesia (sedation with sevoflurane, n = 60) were compared in 130 patients undergoing carotid endarterectomy. Parameters of central hemodynamics and cerebral blood circulation were investigated. Results. It was found out that anesthesia with sevoflurane supported an effective level of central hemodynamics and provided a higher level of cerebral blood flow and was associated with statistically significant (11.9%) reduction in the number of neurological complications versus anesthesia with propofol. Conclusion: Inhalation anesthesia with sevoflurane can be considered the choice of anesthesia in carotid endarterectomy.